Functional characterization of germin family genes contributing to broad-spectrum, quantitative disease resistance in rice - Davidson, Rebecca M., author; Leach, Jan E., advisor (Colorado State University. Libraries, 2009)
Quantitative trait loci (QTL) are predicted to confer broad-spectrum and durable disease resistance. Application of disease resistance QTL in crop improvement programs has been hindered because we lack an understanding of (1) the genes contributing to the QTL-governed phenotype and (2) why certain alleles are more effective than others in conferring resistance. In this study, QTL-associated genes in the germin protein family, germin-like proteins (GLP) and oxalate oxidases (OXO), were identified in the rice genome and their functions were tested. Paralogous multi-gene families underlie the physical QTL regions, with twelve OsGLP members on chromosome (chr) 8 and four OsOXO members on chr 3. Based on shared motifs in 5' regulatory regions and/or protein sequence similarities to cereal orthologues, rice OsGLP genes belong to two germin subfamily groups (GER3 and GER4), and OsOXOs belong to the GER1 group. Conserved sequences for each gene family were used in RNA-interference gene silencing experiments. As more OsGLP genes were silenced, the more susceptible the plants were to two distinct fungal pathogens, Magnaporthe oryzae (Mo) and Rhizoctonia solani (Rs). Similarly, OsOXO-RNAi plants showed enhanced susceptibility to Mo, Rs and the broad host range pathogen, Sclerotinia sclerotiorum. OsGLP alleles were compared in resistant (+chr8 QTL) and susceptible (-chr8 QTL) parental rice lines. Cultivar-specific combinations of OsGLP genes were constitutively expressed and transiently induced by both wounding and Mo infection. In agreement with the silencing data, expression profiles suggest that GER4 subfamily members are involved in rice defense response. Transient induction occurred before fungal penetration of the plant cuticle, and differential expression between resistant and susceptible cultivars correlated with differential hydrogen peroxide accumulation after fungal infection and abiotic stresses. Gene silencing data confirms the roles of OsGLP and OsOXO as contributors to broad-spectrum, basal disease resistance in rice. Studies of allelic diversity among rice varieties suggest that regulation of OsGLPs may explain the effectiveness of resistant alleles compared to susceptible. Germin family proteins are encoded by developmentally regulated gene families in rice and across plant taxa. The germin subfamily members studied here have acquired functions in broad-spectrum defense responses and are important loci for crop improvement.
Keywords: disease resistance; gene silencing; germin; oxalate oxidases; quantitative trait loci; molecular biology; plant pathology